Marker Assisted Selection of xa5, xa13 and Xa21 Gene in Breeding Populations Derived from Karma Mahsuri x IRBB 59 - Kotasthane , A J; Gaikwad, N J (Plantae Scientia, 2021)
Bacterial leaf blight, caused by the Gram negative bacterium Xanthomonas oryzae pv. oryzae (Xoo), is a serious disease throughout the rice growing world. Resistant cultivars are the primary and most effective means of control. Marker assisted selection (MAS) can help in screening more efficiently for the presence or absence of resistant genes. Molecular markers have made it possible to identify and pyramid valuable genes of agronomic importance in resistance rice breeding. In the present study, to incorporate durable resistance against bacterial blight three resistance genes, xa 5, xa13 and Xa21, from an indica donor IRBB 59 were introgressed into high yielding susceptible rice cultivar Karma Mahsuri. Karma Mahsuri is one of the most popular varieties of Chhattisgarh and mega varieties of India. These three genes were pyramided through marker-assisted breeding. For MAS of xa5:- RG556, RM122, RM390, RM13; xa13:-RG136 and RM 230 and Xa21: Xa21 and RM21 are the known linked markers. Markers xa5R and xa5S specific for xa5 resistant and susceptible genes respectively, xa13Pro for xa13 gene and PT248 for Xa21 gene obtained from Dr Sundaram (DRR, Hyderabad) were also used in the present study for MAS. High-resolution maps generated in silico around xa5 and xa13 will be useful for the precise placement of a gene of interest and the analysis of regional and sub-regional rates of recombination and appropriate combinations of markers for marker assisted selection in plant-breeding. In Karma Mahsuri X IRBB 59 cross we got Three lines (03) containing three gene (xa5, xa13 and Xa21), Twenty three (23) line contain a combination of xa5 & xa13, only one (01) with xa5 and Xa21. There were eight lines with xa5 gene Seventeen (17) lines with xa13 gene. We therefore report herein the development of nil, two and three gene pyramids of xa5, xa13 and Xa21 in the background of Karma Mahsuri.